Prevalensi dan Derajat Infeksi Dactylogyrus sp. pada Insang Benih Bandeng (Chanos chanos) di Tambak Tradisional, Kecamatan Glagah, Kabupaten Lamongan [Prevalence and Infection Level of Dactylogyrus sp. on Gill of Milkfish Juvenile (Chanos chanos) in Traditional Pond, Glagah Subdistrict, Lamongan Residence] - Faisol Mas'ud (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract The aim of research was to know prevalence and infection level of Dactylogyrus sp. on gill of milkfish juvenile (Chanos chanos) in traditional pond, Glagah Subdistrict, Lamongan Residence. It was using sample of 5 milkfish juvenile and for each treatment three replication. Researh design was Complete Random Design and continued by Analysis of Variance (ANOVA) and Least Significant Difference (LSD) 5%. The result showed that prevalence of Dactylogyrus sp. on gill of milkfish juvenile in Dalung village and Pedurungan village were significantly of 53.33% and 86.67%, respectively. Furthermore, infection level of Dactylogyrus sp. on gill of milkfish juvenile were significantly on all of area.